Post-Pandemic Economic Recovery Strategy Through The UMKM and Tourism Sector: Experience From Indonesia - Sobrotul Imtikhanah; Mega Metalia (Agregat: Jurnal Ekonomi dan Bisnis, 2022)
The Covid-19 outbreak, which has infected almost all parts of the world, has an impact on all dimensions, be it social, political and economic. The impact is felt, especially by UMKM and tourism, because these condsector has a great influence on economic growth, therefore there needs to be a special strategy in economic recovery. The aim of this paper is to look at the state of the world economy due to the pandemic, economic recovery strategies in the UMKM sector and tourism. The method used is descriptive qualitative by using a content analysis technique approach and literature study. From the results of this study, there are several countries that provide salary subsidies to workers, encourage the development of innovation, relaxation of loans and digitalization in both UMKM and tourism. Meanwhile, Indonesia's economic recovery strategy in the UMKM sectoris: providing assistance to business actors, providing tax incentives, credit relaxation and restructurization, expansion of working capital financing, product support, and e-learning training. Then the economic recovery strategy in the tourism sector, developing tourism products, developing tourist destinations, developing tourism human resources, developing tourism institutions, and managing tourism infrastructure.